The Rise of David Levinsky - Cahan, Abraham, 1860-1951 (Salt Lake City, UT : Project Gutenberg, 2001)
"The Rise of David Levinsky" by Abraham Cahan is a novel published in 1917. It tells the story of a Russian Jewish immigrant's journey from abject poverty to wealth in America. Born in the Russian Empire, David loses his mother to violence and abandons his Talmudic studies to pursue a new life. He arrives in New York as a penniless greenhorn, slowly shedding his old-world ways while navigating love, labor, and the promises of his adopted homeland. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Rise_of_David_Levinsky
Release date is 2001-09-01
Keywords: Psychological fiction; Immigrants -- Fiction; Jewish men -- Fiction; Assimilation (Sociology) -- Fiction; Clothing trade -- Fiction; Millionaires -- Fiction; Jewish fiction; Jews -- New York (State) -- New York -- Fiction; Jews -- Russia -- Fiction; Lower East Side (New York, N.Y.) -- Fiction